Comparative sexual selection in field and laboratory in a guild of sepsid dung flies. (May 2021) - Blanckenhorn, Wolf U.; Baur, Julian; Roy, Jeannine; Puniamoorthy, Nalini; Busso, Juan Pablo; Schäfer, Martin A.; Rohner, Patrick T.
Abstract : Phenomenological and behavioural studies have greatly advanced the study of natural selection. Field studies of selection well appraise the natural situation, but is this also true for laboratory studies, which are typically more mechanistic? We compared precopulatory sexual selection (mating differential based on pairing success) in field and laboratory of several closely related, ecologically similar black scavenger dung flies (Diptera: Sepsidae). Selection on fore femur (sexual trait) and wing size (nonsexual trait) and shape varied considerably among seven species and continental populations in agreement with variation in their mating system and sexual size dimorphism. Selection on trait size was mostly positive or nil, but never significantly negative, implying mating advantages of large males in most species. Strongest selection was found in species/populations with male-biased size dimorphism, associating evolutionary shifts from female- to male-biased dimorphism with intensified sexual selection for large male size by adding male –male competition to a mating system previously driven primarily by female choice. Although sexual selection on shape was closely aligned with allometric shape variation, selection on fore femur shape was more consistent than selection on wing shape, which was absent in most species. Sexual selection intensities, but not necessarily the underlying behavioural mechanisms, were overall similar in field and laboratory, suggesting that laboratory assessments well represent the natural situation. If this conclusion can be generalized, it would lend credence to the strategy of using controlled laboratory mating studies to better understand natural selection, behaviour and ecology, at least for smaller animals that can be held in captivity. Highlights: We estimated mating differentials on body size in a guild of sepsid fly species. Despite varying mating systems, larger males in general had a mating advantage. Sexual selection was stronger in species with male-biased sexual size dimorphism. Sexual selection was similar in field and laboratory for a given species. Given similar environments, lab studies well reflect the field situation.